2015
DOI: 10.1016/j.jpeds.2015.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oral Methadone in the Treatment of Neonatal Abstinence Syndrome: A Pilot Study

Abstract: Objective To characterize the population pharmacokinetic (PK) of oral methadone in neonates requiring pharmacologic treatment of neonatal abstinence syndrome (NAS) and to develop a PK model towards an evidence-based treatment protocol. Study design Based on a methadone dosing protocol, serum concentrations of methadone and its metabolites were assessed via high performance liquid chromatography-tandem mass spectrometry from dried blood spots. Population PK analysis was performed to determine the volume of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 36 publications
1
68
0
1
Order By: Relevance
“…Simulations were conducted with a nominal dose but not the actual dose, which may result in an overprediction of the clinical data. Also, drug screens and/or maternal reporting revealed that 60% of the newborns were exposed to multiple opioids and 40% were exposed to opioids plus additional substances of abuse (ie, cocaine, marijuana, benzodiazepines) in utero . Fetal exposure to certain compounds have been shown to alter organ function, thereby potentially altering methadone concentrations .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simulations were conducted with a nominal dose but not the actual dose, which may result in an overprediction of the clinical data. Also, drug screens and/or maternal reporting revealed that 60% of the newborns were exposed to multiple opioids and 40% were exposed to opioids plus additional substances of abuse (ie, cocaine, marijuana, benzodiazepines) in utero . Fetal exposure to certain compounds have been shown to alter organ function, thereby potentially altering methadone concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…The blood‐to‐plasma ratio in neonates was estimated based on the fixed adult erythrocyte‐to‐plasma ratio and neonatal hematocrit values (), as described in the Supplementary Material S1 of Emoto et al These parameters are summarized in Table . The pharmacokinetic profiles of R‐ and S‐methadone were simulated according to the actual dosing regimen for each of the 20 full‐term newborns with no known compromising illnesses treated for NAS, and then the simulated results were compared to the time‐course concentration data observed in the PK study in newborns with NAS . The sum of R‐ and S‐methadone AUC was used to predict the performance of the simulations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of The Journal , Wiles et al 3 provide initial pharmacokinetic data for oral methadone use in infants with NAS. The literature supports the use of an opioid to treat opioid withdrawal 4 ; however, data supporting one treatment protocol over another are lacking.…”
mentioning
confidence: 99%